Micrometre-Sized Porous Polymer Beads as Heterogeneous Molecular Catalysts - Stammler, Michael B.; Bauer, Anton; Alkhurisi, Mohammed H.; Gigl, Ferdinand; Wisser, Florian M. (Chemie Ingenieur Technik, 2023)
Porous polymers have great potential as versatile, chemically stable catalyst supports. Yet, shaping of the resulting powders remains a challenge. Here, we demonstrate the use of suspension polymerisation to design micrometre-sized porous polymers beads containing metal binding sites. The good accessibility of the binding sites ensures high catalytic activity, which is demonstrated for two model reactions: photochemical CO2 reduction and transfer hydrogenation of aromatic ketones. Importantly, the shaping of the host material does not affect the catalytic activity of the active site.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Heterogeneous catalysis; Micrometre-sized beads; Porous organic polymer; Rhodium; Suspension polymerisation